DIGITAL PEDAGOGY AND ITS TOOLS - Aziza Tolibovna Kurbanova (Modern American Journals, 2025)
This article explores the concept of digital pedagogy, its core principles, and its significance in the modern educational environment. The paper highlights the role of digital technologies in transforming teaching methods, enhancing learner engagement, and developing digital competencies among students. Particular attention is given to the use of interactive tools, multimedia resources, online platforms, and artificial intelligence in organizing flexible, personalized, and student-centered learning. The author analyzes the pedagogical dimensions of digital didactics and the dynamics of teacher-learner interaction in a digital educational space. The article concludes that the effective integration of digital tools can lead to higher-quality education and more adaptive learning environments.
Keywords: Digital pedagogy, educational technologies, digital teaching tools, interactive learning, multimedia resources, digital didactics, personalized learning, digital competencies, artificial intelligence in education